Efficacy of annual colonoscopic surveillance in individuals with hereditary nonpolyposis colorectal cancer - Engel, Christoph; Rahner, Nils; Schulmann, Karsten; Holinski-Feder, Elke; Goecke, Timm O.; Schackert, Hans K.; Kloor, Matthias; Steinke, Verena; Vogelsang, Holger; Möslein, Gabriela; Görgens, Heike; Dechant, Stefan; et al. (Clinical gastroenterology and hepatology, 2010)
Background & Aims - Individuals with hereditary nonpolyposis colorectal cancer (HNPCC; Lynch syndrome) have a high risk for developing colorectal cancer (CRC). We evaluated the efficacy of annual surveillance colonoscopies to detect adenomas and CRCs. - Methods - In a prospective, multicenter cohort study, 1126 individuals underwent 3474 colonoscopies. We considered individuals from 3 groups of HNPCC families: those with a pathogenic germline mutation in a mismatch repair gene (MUT group), those without a mutation but with microsatellite instability (MSI group), and those who fufilled the Amsterdam criteria without microsatellite instability (MSS group). - Results - Compliance to annual intervals was good, with 81% of colonoscopies completed within 15 months. Ninety-nine CRC events were observed in 90 patients. Seventeen CRCs (17%) were detected through symptoms (8 before baseline colonoscopy, 8 at intervals >15 months to the preceding colonoscopy, and 1 interval cancer). Only 2 of 43 CRCs detected by follow-up colonoscopy were regionally advanced. Tumor stages were significantly lower among CRCs detected by follow-up colonoscopies compared with CRCs detected by symptoms (P = .01). Cumulative CRC risk at the age of 60 years was similar in the MUT and MSI groups (23.0% combined; 95% confidence interval [CI], 14.8%-31.2%) but considerably lower in the MSS group (1.8%; 95% CI, 0.0%-5.1%). Adenomas at baseline colonoscopy predicted an earlier occurrence of subsequent adenoma (hazard ratio, 2.6; 95% CI, 1.7-4.0) and CRC (hazard ratio, 3.9; 95% CI, 1.7-8.5), providing information about interindividual heterogeneity of adenomas and kinetics of CRC formation. - Conclusions - Annual colonoscopic surveillance is recommended for individuals with HNPCC. Less intense surveillance might be appropriate for MSS families.
Available online: 14 October 2009
Gesehen am 16.03.2023